Frequency of Intraoperative Complications in Patients Undergoing Laparoscopic Cholecystectomy - Zaman, Ahmed; Faraz, Ahmad (Indus Journal of Bioscience Research, 2025)
Background: Laparoscopic cholecystectomy is the standard treatment for gallstone disease, offering advantages such as reduced postoperative pain, shorter hospital stays, and faster recovery. Despite being considered safe, intraoperative complications such as liver bed injury, bleeding from Calot’s triangle, trocar site bleeding, and bile leakage can occur and may influence surgical outcomes. Limited regional data exist regarding the frequency and risk factors of these complications in Peshawar. Objective: To find out the frequency of intra operative complication in patients undergoing laparoscopic cholecystectomy. Study Design: Descriptive observational study. Duration and Place of Study: The study was conducted in the Department of General Surgery, Lady Reading Hospital, Peshawar, from December 2024 to May 2025. Methodology: A total of 236 patients aged 18–65 years undergoing laparoscopic cholecystectomy were included through consecutive non-probability sampling. Patients with obstructive jaundice, gallbladder malignancy, or pregnancy were excluded. Complications were documented intraoperatively as liver bed injury, bleeding from Calot’s triangle, trocar site bleeding, or bile leakage. Results: Among 236 patients (mean age 41.18±13.86 years, 66.5% female), the frequencies of complications were: liver bed injury 8.1%, bleeding from Calot’s triangle 4.7%, trocar site bleeding 8.1%, and bile leakage 7.2%. Significant associations were found between liver bed injury and age ≤45 years (p=0.030), bile leakage and female gender (p=0.049), bleeding complications and BMI >25 kg/m² (p=0.008, p=0.006), and higher rates of liver bed injury and Calot’s bleeding in rural patients (p=0.015, p=0.026). Conclusion: Intraoperative complications during laparoscopic cholecystectomy occur with acceptable frequencies but are significantly influenced by age, gender, BMI, and place of residence, emphasizing the importance of careful preoperative assessment and surgical precision.